Influencing Factor Analysis and Prediction Model of Emergency Caesarean Delivery for Advanced-Age Nulliparous Women at the Time of Hospitalization - Ryosuke Arakaki; Wataru Isono; Hiroaki Fukuda; Junya Tanaka; Arisa Minamino; Shiko Hayashi (Journal of Family and Reproductive Health)
Objective: In Japan, the number of nulliparous pregnant women of advanced age, defined as 35 years or older, has increased, and the age range has lengthened towards older age with the increased use of infertility treatments. Given this trend, adverse labour outcomes, such as emergency caesarean delivery (ECD), are expected to increase. Therefore, by focusing mainly on maternal age and infertility treatment history, we aimed to establish a new prediction model for the likelihood of ECD after identifying the influencing factors related to maternal and labour-related characteristics. Materials and methods: The medical records of 1,521 pregnant women who were nulliparous between 2017/4/1 and 2024/3/31 at our hospital were retrospectively reviewed. First, for the 675 women who were aged 30 years old or more, we calculated the rates of ECD in 8 groups classified according to maternal age, infertility treatment, and other variables. Next, we performed multivariate logistic regression analysis to assess the effect of each representative factor and established a prediction model based on the number of factors that were significant in the multivariate analysis. Results: Simple comparisons classified by maternal age revealed a constant increase in the rate of ECD with increasing maternal age, and multivariate analysis revealed 7 significant factors, namely, advanced maternal age, history of using assisted reproductive techniques (ART), small height, high Body mass index (BMI), low Bishop score, late-term delivery, and large infant. In the prediction model constructed with these 7 factors, the rate of ECD increased as the number of these factors increased. Conclusion: The negative impact of advanced maternal age, namely, 40 years or older, and ART history, on labour outcome is clear. A new prediction model has the potential to identify patients with an extremely high probability of needing an ECD. These results may indicate that the management of the labour process will become more difficult in the future.